A Digital Rights Management System based on Cloud - Franco Frattolillo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In the current Internet, digital entertainment contents, such as video or audio files, are easily accessible due to the new multimedia technologies and to broadband network connections. This causes considerable economic loss to global media players since digital contents, once legitimately obtained, can be illegitimately shared through file sharing services on the Internet. Digital Rights Management (DRM) systems have been proposed to support the protection of copyrighted digital contents. Even though such systems have been widely adopted and promoted by global media players, they are based on proprietary mechanisms that usually work only in closed, monolithic environments. In this regard, systems based on watermarking technologies appear more suited to protect digital copyrighted content. This paper describes the implementation scheme of a DRM system able to ensure the copyright protection of digital content according to an innovative buyer-friendly watermarking protocol. The DRM system has been implemented by exploiting a cloud environment in order to improve the overall performance of the system. In particular, cloud behaves as a service infrastructural provider, since the content provider involved in the watermarking protocol uses cloud to speed up the watermark embedding process and to save storage and bandwidth costs needed to store and to deliver protected contents.